Screening for sleep apnea in the young hypertensive: evidence from a case-control study in Malaysia - Asha'ari, Zamzil Amin; Hasmoni, Mohamed Hadzri; Ab Rahman, Jamalludin; Raja Lope Ahmad, Raja Ahmad Al'konee (2012)
Objective : Younger patients with sleep apnea have higher risks of cardiovascular mortality compared to their normal counterpart. Yet, it remains a continued struggle to find a suitable cost-effective means of screening for sleep apnea in the young population. We conducted a case-control study of the possible association between sleep apnea and hypertension in a younger population in Malaysia. Method : We analyzed data on sleep disordered breathing (based on a polysomnography study), body mass index (BMI), neck circumference, upper airway size, habitus and health history in 90 hypertensive and 90 non-hypertensive participants in a clinic-based setting. Independent t-test, chi-square, multivariate analysis and binary logistic regression models were used for case-control comparison.